ATRAKSI WISATA DI ULU KASOK DESA PULAU GADANG KECAMATAN XIII KOTO KAMPAR - Ratih Purwaningsih; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
In the title of this research there is a problem, which as it is known that the Ulu Kasok attraction is a tourist attraction that has recenly attracted a lot of interest from local visitors. However, due to the lack of attractions of that are the main attraction of this object, local visitors are gradually decreasing. This object is in great demand by people because of its scenery which is similar to the tourist attraction that is highly desired by many people, namely Raja Ampat, there for the perpose of this research is to find out which attractions can make this Ulu Kasok tourist attraction an object of interest to the public many people. This study uses a qualitative method with a qualitative descriptive approach and analyzes the data by conducting observations, documentation and interviews wiyh visitors local communities and the departement that manages them. After conducing interviews with various informants the researcher concluded that the Ulu Kasok tourist attraction did not get the attention of the management in increasing the attractions that became the data of attraction for tourists or visitor who came to the place. Keywords : Attractions, Tours